Continuous Renal Replacement Therapy for Cytokine Storm in Diabetic Kawasaki Shock Syndrome - Zhijiang Zhou; Ping Ling; Rong Tang; Ye Chen; Yi Lin; Xuexin Wang; Sha Wang (Pediatrics, 2026)
To report the successful use of continuous renal replacement therapy (CRRT) in a child with type 1 diabetes mellitus (T1DM) and intravenous immunoglobulin (IVIG)–refractory Kawasaki disease shock syndrome (KDSS). A 3-year, 10-month-old boy with poorly controlled T1DM and autoimmune thyroiditis presented with KDSS and diabetic ketoacidosis. Despite IVIG and high-dose aspirin, he developed refractory shock and metabolic acidosis. Continuous venovenous hemodiafiltration was initiated, leading to rapid hemodynamic stabilization, resolution of hyperinflammation, and metabolic normalization. CRRT may serve as a rescue therapy in critically ill children with concurrent cytokine storm and metabolic crisis, particularly when standard immunomodulatory therapies fail.